2020
DOI: 10.1186/s11658-020-00215-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC2 inhibits hypoxia-induced pulmonary artery smooth muscle cell proliferation and migration by regulating the miR-222/ING5 axis

Abstract: Background: Pulmonary arterial hypertension (PAH) is often characterized by cell proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs). LncRNA cancer susceptibility candidate 2 (CASC2) has been revealed to be involved in PASMC injury in hypoxia-induced pulmonary hypertension. However, the exact molecular mechanisms whereby CASC2 regulates PASMC proliferation and migration are still incompletely understood. Methods: The expression levels of CASC2, miR-222 and inhibitor of growth 5 (ING5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…LncRNAs TUG1 and NONRATT015587.2, as ceRNAs, have been reported to have an impact on vascular remodelling in PH [ 25 , 26 ]. LncRNA CASC2 and Hoxaas3 regulate PASMC proliferation and migration in HPH by influencing the expression of miR-222 and homeobox a3, respectively [ 27 , 28 ]. LncRNA PAXIP1-AS1 plays an important role in PH by affecting PH-specific transcriptional programmes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs TUG1 and NONRATT015587.2, as ceRNAs, have been reported to have an impact on vascular remodelling in PH [ 25 , 26 ]. LncRNA CASC2 and Hoxaas3 regulate PASMC proliferation and migration in HPH by influencing the expression of miR-222 and homeobox a3, respectively [ 27 , 28 ]. LncRNA PAXIP1-AS1 plays an important role in PH by affecting PH-specific transcriptional programmes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence has demonstrated that lncRNAs play important roles in the development of various tissues, such as the brain [ 29 ], liver [ 30 ], heart [ 31 ], testis [ 32 ], ovary [ 33 ], kidney, uterus [ 34 ], muscle [ 35 ], mammary gland [ 36 ], and inner ear [ 37 ]. However, few studies have been conducted on the potential role of lncRNAs in mammalian hair follicle development and wool curvature.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs associated with muscular atrophy in disease are expected to be identified in the future, and they may function by many different mechanisms. In addition, lncRNAs are reported to participate in various physiological and pathological processes, such as cancer ( Lu et al, 2013 ; He et al, 2014 ; Sun et al, 2014 ; Zhuang et al, 2014 ; Yin et al, 2015 ; Zhou et al, 2015 ; Zou et al, 2016 ; Wang J. et al, 2017 ), aging ( Boon et al, 2016 ; Su et al, 2019 ), muscle development ( Ballarino et al, 2018 ; Jin et al, 2018 ; Zhang et al, 2018b ), and their associated disorders ( Han et al, 2020 ). A better understanding of the roles of miRNAs and lncRNAs and their corresponding signaling pathways in regulating skeletal muscle atrophy in cachexia and other diseases will eventually help elucidate the mechanisms underlying muscle wasting and may contribute to the design of new strategies for the prevention, diagnosis, and treatment of muscle-wasting diseases.…”
Section: Discussionmentioning
confidence: 99%